miR-92a and integrin expression in fibrovascular membranes in proliferative diabetic retinopathy - Luo, Qianyi; Hajrasouliha, Amir R.; Bhatwadekar, Ashay D. (Frontiers in Ophthalmology, 2023)
Diabetic retinopathy (DR) is a leading cause of vision impairment. The proliferative form of DR (PDR) involves fibrovascular membrane (FVM) formation at the vitreoretinal interface. MicroRNAs (miRNAs) are a class of non-coding RNA molecules that play an important role in gene regulation; a single miRNA could regulate multiple genes. We previously reported that miR-92a, a suppressor of integrins α5 and αv, was downregulated in DR. Considering the integrin’s role in FVM pathology and the potential involvement of miR-92a in DR, we asked a question whether miR-92a could play a critical role in FVM pathology. We collected the FVM and epiretinal membranes of individuals with PDR and macular pucker (control) undergoing pars plana vitrectomy. The frozen sections of membranes were stained for α5 and αvβ3 integrins. The miR-92a levels were assessed using real-time quantitative PCR. The FVMs of individuals with PDR stained brighter for integrin subunits α5 and αvβ3 compared to the epiretinal membranes of subjects with macular pucker. miR-92a levels were decreased in FVM subjects. In conclusion, our studies demonstrate that miR-92a decrease is associated with an increase in integrins α5 and αvβ3, thus contributing to the inflammatory milieu in PDR.